A FIT‐binding protein is involved in modulating iron and zinc homeostasis in Arabidopsis. (23rd May 2018) - Chen, Chun‐Lin; Cui, Yan; Cui, Man; Zhou, Wen‐Juan; Wu, Hui‐Lan; Ling, Hong‐Qing
Abstract: Fe and Zn are essential micronutrients for plant growth, and the interrelationship regarding their homeostasis is very complicated. In this study, we identified a FIT‐binding protein (FBP) using the yeast two‐hybrid system. The C‐terminus of FBP binds to the bHLH domain of FIT, abolishing the DNA‐binding capacity of FIT. Knockout of FBP results in an enhanced expression of NAS genes and a higher nicotianamine content, and the fbp mutant exhibits tolerance to excessive Zn. Physiological analyses reveal that the mutant fbp retains a larger amount of Zn in roots and transfers a greater proportion of Fe to shoots than that in wild type under Zn‐excessive stress. As FBP is expressed in the root stele, the negative regulation caused by sequestration of FIT is restricted to this tissue, whereas other FIT‐regulated genes, such as IRT1 and FRO2, which mainly expressed in root epidermis, do not show transcriptional upregulation in the fbp mutant. As an antagonistic partner, FBP offers a new approach to spatially fine‐tune the expression of genes controlled by FIT. In conclusion, our findings provide a new insight to understand the interrelationship of Fe and Zn homeostasis in plants. Abstract : Fe and Zn are essential micronutrients for plant growth, but they are also toxic heavy metals. The balancing homeostasis of Fe and Zn is complicated and tightly regulated in plants. In this study, we identified a novel FIT‐binding protein (FBP), which sequestrates FIT (a key transcriptional factor of iron homeostasis) in root stele to modulate the expression of NAS genes for balance of Fe and Zn homeostasis in Arabidopsis .